Intellectual property safe - First-to-File and First-to-Invent system - Cecilia Young (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
All countries use the First-to-File system. An inventor may feel very tense about the time race and the physical and cyber security of his intellectual properties. Biomedical researchers and inventors are particularly vulnerable since most of them may not possess enough IT knowledge to maintain cyber security. An Intellectual Property Safe System to protect the initial draft and/or prototypes is suggested.